Employment Protection, Job Insecurity, and Job Mobility - Marco Bertoni; Simone Chinetti; Roberto Nistico (Institute of Labor Economics (IZA), 2023)
This study leverages the Italian Jobs Act reform as a natural experiment to examine the impact of reduced employment protection on job insecurity and job mobility. The reform significantly lowered protection for open-ended contract workers in large firms hired after March 7, 2015, and introduced a sharp discontinuity in severance pay at 2-year tenure. Treated employees exhibit increased fear of job loss and higher termination rates. The higher job insecurity prompts workers in low-pay sectors and in low-quality firms to actively pursue job mobility, transitioning towards higher-paying positions. Conversely, workers in high-paying sectors respond by intensifying their efforts to secure their existing jobs. Crucially, all effects disappear for workers above the 2-year tenure threshold, when they become entitled to a 50% higher severance pay. These findings emphasize a complex trade-off behind the design of employment protection systems, as addressing early-stage insecurity with tailored social insurance may counteract upward mobility effects.
Keywords: J22; J28; J41; J65; 330; employment protection; job insecurity; job mobility; on-the-job search